Cyrus, Yhwh’s Bird of Prey (Isa. 46.11): Echoes of an Ancient Near Eastern Metaphor - Chan, Michael J. (Journal for the study of the Old Testament, 2010)
In Isa. 46.11, Cyrus is described as a ‘bird of prey’ (‭ט ע‬), a designation that poses a seemingly difficult translational and interpretational problem for many commentators. Generally speaking, two solutions have been forwarded: (1) some, discontented with the apparently awkward parallelism between ‘a bird of prey’ (‭ט ע‬) and ‘his man of purpose’ (‭ו ת צ ע ש א‬), have resorted to speculative and questionable emendations; (2) other commentators maintain the MT, citing as support Xenophon’s description of a golden eagle that served as Cyrus’s ensign or accepting the metaphor as an image of swiftness and ferocity. The important role played by bird of prey imagery in the royal propaganda of the ancient Near East and Egypt, however, is rarely considered. In this article it is proposed that the image of Cyrus as a ‘bird of prey’ (‭ט ע‬) is not strange, awkward, or in need of emendation; nor is it necessary to turn to the oft-cited reference in Xenophon for an explanation. Rather, the image arises out of the author’s familiarity with a larger convention that associates royal monarchs and their military activities with behavior of birds of prey.